2017
DOI: 10.3892/ol.2017.6094
|View full text |Cite
|
Sign up to set email alerts
|

Blueberries inhibit cyclooxygenase-1 and cyclooxygenase-2 activity in human epithelial ovarian cancer

Abstract: Abstract. Ovarian cancer (OC) is the sixth and eighth leading cause of cancer mortality among women in developed and developing countries, respectively. Medical therapy is the main method for the treatment of OC. However, drug toxicity and the marked side effects of chemotherapy limit the usage and therapeutic results of the treatments. Therefore, the identification of multi-target agents with few side effects and high effectiveness is required. Traditional Chinese medicine has been used clinically to treat va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Anthocyanin and anthocyanidin extracts from blueberry can inhibit the proliferation and trigger the apoptosis of B16-F10 cells [ 33 ]. Blueberry consumption (400 mg daily) can reduce tumor size significantly in mice, which inhibited the proliferation of ovarian cancer cells by downregulating the levels of cyclooxygenase-1 and cyclooxygenase-2 [ 34 ].…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…Anthocyanin and anthocyanidin extracts from blueberry can inhibit the proliferation and trigger the apoptosis of B16-F10 cells [ 33 ]. Blueberry consumption (400 mg daily) can reduce tumor size significantly in mice, which inhibited the proliferation of ovarian cancer cells by downregulating the levels of cyclooxygenase-1 and cyclooxygenase-2 [ 34 ].…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…Therefore, the identification of multitarget agents with high effectiveness is required. 37,41 Several reports have shown that either COX-1 or COX-2 is upregulated in EOC. Treatment with COX-1-and COX-2-specific inhibitors may exhibit a therapeutic effect on EOC.…”
Section: Targeting Coxs In the Treatment Of Eocmentioning
confidence: 99%
“…23,36,42,43 Table 1 summarizes the major treatment strategies of EOC and the consequences by targeting COXs. Lin and Li 41 reported that blueberries may affect the progression of EOC by downregulating the levels of COX-1 and COX-2. Eilati et al 44 suggested that targeting PG biosynthesis might also be an effective approach in preventing EOC.…”
Section: Targeting Coxs In the Treatment Of Eocmentioning
confidence: 99%
“…The reactions they catalyze rely on the use of arachidonic acid (AA) as a substrate, obtained through the activity of cytoplasmic phospholipase A2 (cPLA2) from cell membrane phospholipids [15]. Both cyclooxygenase isoforms catalyze the transformation of AA into prostaglandin H2 (PGH2), from which the remaining prostaglandins and thromboxanes are synthesized [16][17][18]. The COX-1 gene expression in most cells is constitutive [19].…”
Section: Introductionmentioning
confidence: 99%